(untitled) - Grewal, Dhruv (New York, 2010)
Marketing 2e is the newest principles of marketing textbook from Dhruv Grewal and Michael Levy, and was created with students' and professors' needs in mind. Students receive a cost-effective, easy to read, focused text complete with study resources (both print and online) to help them review for tests and apply chapter concepts. Professors receive a text that contains all the pertinent information - yet in a more condensed format that is easier to cover by students. Online gradable assignments are provided to utilize the power of the web, making projects more fun for students and automatically grade materials to support instructors.
Keywords: Marketing,Tiếp thị